Evaluating the Efficiency–Emission Trade-Off of Biomass Co-Firing in a Large-Scale Coal-Fired Power Plant: Evidence from Java, Indonesia - Zia Ulhaq; Nur Aini Hidayati (Journal of Business, Social and Technology, 2026)
Background: Biomass co-firing is widely promoted as a low-cost transition strategy to reduce emissions from coal-fired power plants while maintaining the reliability of baseload electricity systems. However, its operational impact on plant efficiency remains insufficiently examined, particularly in developing countries where coal still dominates the energy mix. Objective: This study evaluates the efficiency–emission trade-off of biomass co-firing using monthly operational data from an Indonesian coal-fired power plant over the period 2021–2025. Methods: An Error Correction Model (ECM) is applied to analyze both short-run and long-run relationships among biomass co-firing ratio, thermal efficiency measured by Net Plant Heat Rate (NPHR), and emissions of particulate matter (PM), sulphur dioxide (SO₂), and nitrogen oxides (NOₓ). Results: The findings show that biomass co-firing significantly reduces SO₂ and PM emissions in the long run, confirming its environmental benefits. However, it also leads to a decline in thermal efficiency, indicated by an increase in NPHR as the co-firing ratio rises. In contrast, NOₓ emissions are not significantly affected, suggesting they are more influenced by combustion conditions than fuel substitution. Overall, the results highlight a clear trade-off between emission reduction and efficiency performance. Conclusion: The study concludes that although biomass co-firing supports decarbonization in coal-dependent power systems, its implementation should carefully balance environmental objectives with efficiency losses and operational reliability considerations.